The effect of kinesiological taping on pain, function, and disability in subacromial impingement syndrome- a randomized controlled study - ŞENOCAK, EMRE; YILDIZ ÖZER, AYSEL (My University, 2022)
Objective: Subacromial Impingement Syndrome (SIS) is one of the most common shoulder pathologies that cause pain and lose of function. This study aimed to compare the effects of kinesiological taping and conventional physiotherapy (CP) on pain, functionality, and disability in SIS patients. Materials and Methods: The study was completed with 54 patients aged 18-60 years. By randomization, the participants were divided into two groups: The Intervention Group (IG) and the Control Group (CG). While the CP was performed for ten sessions, kinesiological taping was repeated every three days for the IG. The CG was taken to only ten sessions of CP. The CP was applied for 60x5x2 minutes/day/week. Pain severity, function, and disability were assessed before and after the treatment. Results: There was no difference between the groups in pain severity (p=0.074), function (p=0.565), and disability (p=0.315) scores. On the other hand, there were significant improvements in pain (p=0.001), function (p=0.001), and disability (p=0.005) scores of IG according to intra-group analysis. Similar results were obtained in the CG. However, when the effect sizes of these treatment methods were examined, they did not create a clinically significant superiority compared to each other. Conclusion: Kinesiological taping has been widely used in patients with orthopedic problems. According to our results, kinesiological taping did not have a clinical effect in reducing pain, improving function and disability when applied with CP compared to CP alone. We think that only kinesiological taping may not be sufficient be an alternative to traditional methods in the early term.
Keywords: Subacromial Impingement Syndrome; Taping; Pain; Function; Disability